Implementation of Balance Principles in Banking Credit Agreements (Study of Bank Jateng Purwokerto Wage Market Branch) - Agung Setyawan Tri Nugroho (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2021)
Notary is a public official who is authorized to make an authentic deed. Authentic Deed is a legal document that is very important for banks to secure their transactions, in practice the use of a deed under the hand is still rife in banks. This is evident from the still many uses of standard contracts in credit agreements. Credit agreements whose standard forms are unbalanced to provide a strong legal umbrella in providing consumer protection in the financial services sector. OJK issued Regulation Number: 1 / POJK.07 / 2013, with the entry into force of the POJK, clearly stipulated the principle of balance in the credit agreement The method used in this research is normative juridical method. The data used is secondary data. The results showed that the application of the principle of balance in a banking credit agreement (study in Bank Jateng Cabang Pasar Wage Purwokerto), there were differences in the application of the principle of balance before and after the issuance of POJK, it is clear where the debtor's position in the agreement was weak can be seen if there is a change in Government policy in the economic and monetary sectors which causes the Bank to change all lending rates unilaterally not involving the debtor's approval so that it can be concluded that the principle of balance before POJK is not applied, whereas after the existence of POJK Bank Jateng is in accordance with the position of both creditors and debtors in the agreement in accordance with their rights and obligations. The legal consequences of the credit agreement that does not carry out the principle of balance of the deed based on the provisions above, then the credit agreement with not fulfilling the legal provisions as required by legislation, then the agreement is null and void because the formal conditions are not fulfilled, then the business actor financial services, namely banks, which do not meet the protection elements stipulated in the POJK, may be subject to sanctions regulated in Article 53 POJK. Its legal protection for consumers is repressive based on POJK Article 40. Suggestions for supervision from OJK in assessing and verifying the form of credit agreement at the bank, so that the clauses in the credit agreement do not violate the provisions of the Consumer Protection Act and Regulation Number: 1 / POJK.07 / 2013 concerning Consumer Protection in the Financial Services Sector. Keywords: Authentic Deed, Standard Agreement, Credit Agreement, Financial Services Authority Regulation, Bank BPD.